2013
DOI: 10.1093/humupd/dmt034
|View full text |Cite
|
Sign up to set email alerts
|

IVF and breast cancer: a systematic review and meta-analysis

Abstract: At present, COH for IVF does not seem to impart increased breast cancer risk. Longer follow-up periods, comparisons versus infertile women, subgroup analyses aiming to trace vulnerable subgroups, adjustment for various confounders and larger informative data sets are needed before conclusive statements for the safety of the procedure are reached.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 189 publications
7
52
0
2
Order By: Relevance
“…Along the same lines are the findings of Sergentanis et al [33] who systematically reviewed the literature and concluded that controlled ovarian hyperstimulation for in vitro fertilization does not seem to confer an increased breast cancer risk. However, before definite conclusions concerning the safety of this treatment can be drawn, the authors would like to see longer follow-up periods, appropriate controls and comparisons, and adjustment for various confounders.…”
Section: The Pre-reproductive Phase In Life (Preventing Pregnancy)mentioning
confidence: 66%
“…Along the same lines are the findings of Sergentanis et al [33] who systematically reviewed the literature and concluded that controlled ovarian hyperstimulation for in vitro fertilization does not seem to confer an increased breast cancer risk. However, before definite conclusions concerning the safety of this treatment can be drawn, the authors would like to see longer follow-up periods, appropriate controls and comparisons, and adjustment for various confounders.…”
Section: The Pre-reproductive Phase In Life (Preventing Pregnancy)mentioning
confidence: 66%
“…If estrogen concentration exceeds the threshold value, then its risk occurs as genotoxicity (Metzler et al, 1998). However, the use of fertility medicine and various cancers is not found to be related in some studies (Brinton et al, 2013;Dor et al, 2002;Jensen et al, 2007;Lerner-Geva et al, 2003;Modan et al, 1998;Potashnik et al, 1999;Sergentanis et al, 2014). Some studies claimed that there is no significant relationship between the use of fertility medicine, or other medicine used to stimulate ovaries and breast, and ovarian or endometrium cancer (Jensen et al, 2007;Modan et al, 1998;Potashnik et al, 1999;Zreik et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies claimed that there is no significant relationship between the use of fertility medicine, or other medicine used to stimulate ovaries and breast, and ovarian or endometrium cancer (Jensen et al, 2007;Modan et al, 1998;Potashnik et al, 1999;Zreik et al, 2010). Furthermore, no significant difference was found between women who took IVF treatment and the general population for the formation of breast cancer and ovarian cancer (Brinton et al, 2013;Dor et al, 2002;Lerner-Geva et al, 2003;Sergentanis et al, 2014;Venn et al, 1999Venn et al, , 2001. According to a study conducted on 29,700 IVF patients, ovarian, breast, and uterine cancer formation in patients is not higher than the general population's cancer incidence rates (Venn et al, 1999(Venn et al, , 2001.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1-2). Although a direct relationship between fertility treatments and breast cancer has not been established (Sergentanis et al, 2014), some experts have pointed out that questions still remain. Dr. Kala Visvanathan, an associate professor of oncology and epidemiology at Johns Hopkins explained, "The data so far doesn't suggest that there is a link when you look at it overall…Whether there is a link between subgroups of individuals is yet to be known…whatever is causing the infertility may also put women at higher risk for cancer (Cohn, 2011, paras.…”
Section: Broader Discourses That Contend With Celebrity Storiesmentioning
confidence: 99%